How Does Regional Income Affect Regional Spending? - Tirtana, Dodi; Pradani, Tiara; Hayati, Jurni (Journal of International Conference Proceedings, 2023)
This research aims to know the influence of regional income to regional spending. Areas of the research around Indonesia`s provinces. The research ensures significantly in its potential to shed light on how regional governments can effectively manage their budgets to foster economic growth and development. The analysis used is multiple linear analysis with the help of the STATA 14 application. The data used is data on Regional Spending, Regional Original Income, Transfers to Regions, and Village Funds, and Other Income for 2020-2022 in Indonesia’s provinces taken from the Ministry of Finance Republic of Indonesia. The findings of the study reveal a noteworthy impact of Regional Original Income and Transfers to Regions, and Village Funds on Regional Spending. Nevertheless, the research outcomes also indicate the absence of a significant effect between Other Income and Regional Spending. The importance of Original Regional Income, Transfers to Regions, and Village Funds in making decisions regarding the allocation and use of the budget for Regional Spending. The implication of this research is that regional governments can consider increasing Regional Original Income and managing Funds Transferred to Villages and Regions effectively to support better Regional Spending.